Efficiency analysis of apple and grape producers: A case study of Hungarian SMEs’ producing apples and grapes in 2021 - Nouar, Dalila; Popovics, Péter András (Studia Mundi – Economica, 2023)
In recent years, the world has experienced unforeseen events that have greatly affected the population and the economy. It is important to analyze how the agricultural sector has responded to these events and assess its effectiveness as its performance is always vital, in peaceful periods but even more during the highly uncertain period we have been facing these last years. In Hungary, the most significant fruit production is the cultivation of apples. The specificity of apples, compared to other fruits, is that they can be stored and consumed in their original form all year round. Over the years, however, the final use of apple production has changed, as today most of it is intended for industrial processing in Hungary. The grapes are also consumed as a fruit during a short period of the year. However, a minimal proportion of the grapes are consumed freshly, and most of it is used instead to make the products of the winery. Overall, the country's apple and grape fields have been steadily decreasing over the years. The yield is fluctuating for both apples and grapes, however, the grape yield has been steadily decreasing over the past 5 years. How do these two sectors operate in 2021, one year after the start of Covid-19? This research aims to provide a comprehensive picture of the apple and grape growing sector and then to specifically analyze the financial efficiency of Hungarian small and medium-sized enterprises operating in those two sectors in 2021.